Mother Knowledge Of The Use Of Herbal Plants In Overcoming Nutritional Status Of Toddler - Fatmawati, Nurul; Yesvi Zulfiana; Sri Handayani (Journal for Quality in Public Health, 2023)
The toddler period (golden period) is a golden period that is very sensitive to the environment and this period lasts very short and cannot be repeated. During this critical period, toddlers' brains are more plastic. Brain plasticity in toddlers has positive and negative sides. On the positive side, toddlers' brains are more open to the learning and enrichment process. On the negative side, toddlers' brains are more sensitive to unsupportive environments such as inadequate nutritional intake. Herbal plants are plants that have medicinal properties in healing and preventing disease. The aim of this research is how mothers know about the use of herbal plants in dealing with the nutritional status of toddlers. This research is non-experimental research with a descriptive research design. The results of this study show that the knowledge of mothers of toddlers regarding the use of herbal plants is that the majority of mothers have good knowledge as many as 102 mothers (92%). Keywords: Herbal plants, nutritional status, toddlers.